Axial Involvement in Psoriatic Arthritis cohort (AXIS): the protocol of a joint project of the Assessment of SpondyloArthritis international Society (ASAS) and the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) - Poddubnyy, D; Baraliakos, X; Van den Bosch, F; Braun, J; Coates, LC; Chandran, V; Diekhoff, T; van Gaalen, FA; Gensler, LS; Goel, N; Gottlieb, AB; van der Heijde, D; et al. (SAGE Publications, 2021)

(untitled)
Background: Involvement of the axial skeleton (sacroiliac joints and spine) is a relatively frequent manifestation associated with psoriatic skin disease, mostly along with involvement of peripheral musculoskeletal structures (peripheral arthritis, enthesitis, dactylitis), which are referred to as psoriatic arthritis (PsA). Data suggest that up to 30% of patients with psoriasis have PsA. Depending on the definition used, the prevalence of axial involvement varies from 25% to 70% of patients with PsA. However, there are currently no widely accepted criteria for axial involvement in PsA.Objective: The overarching aim of the Axial Involvement in Psoriatic Arthritis (AXIS) study is to systematically evaluate clinical and imaging manifestations indicative of axial involvement in patients with PsA and to develop classification criteria and a unified nomenclature for axial involvement in PsA that would allow defining a homogeneous subgroup of patients for research.